2013
DOI: 10.1016/j.bbi.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Forced treadmill exercise training exacerbates inflammation and causes mortality while voluntary wheel training is protective in a mouse model of colitis

Abstract: The purpose of this study was to examine whether exercise training reduced inflammation and symptomology in a mouse model of colitis. We hypothesized that moderate forced treadmill running (FTR) or voluntary wheel running (VWR) would reduce colitis symptoms and colon inflammation in response to dextran sodium sulfate (DSS). Male C57Bl/6J mice were randomized to sedentary, moderate intensity FTR (8–12 m/min, 40 min, 6 weeks, 5x/week), or VWR (30 days access to wheels). DSS was given at 2% (w/v) in drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 38 publications
(40 reference statements)
9
113
6
2
Order By: Relevance
“…Other animal studies supported the exercise-induced increase in butyrate-producing bacteria [76], however results might vary according to the protocol employed (voluntary-versus controlled exercise) [77]. observed that voluntary wheel running prevented weight gain and altered microbiota, reequilibrating major-phylum levels.…”
Section: Animal Studiesmentioning
confidence: 98%
“…Other animal studies supported the exercise-induced increase in butyrate-producing bacteria [76], however results might vary according to the protocol employed (voluntary-versus controlled exercise) [77]. observed that voluntary wheel running prevented weight gain and altered microbiota, reequilibrating major-phylum levels.…”
Section: Animal Studiesmentioning
confidence: 98%
“…38 Despite these parallel results linking improvements in T2DM and obesity symptoms to any form of exercise, there are differences between forced and voluntary exercise regarding other physiological outcomes. For example, mice consuming a high-fat diet have shown reduced inflammation when given access to running-wheels; 15 conversely, forced exercise may promote inflammation 39 and differently affect the gut microbiome compared to voluntary wheel-running in rodent models. 40 Future studies investigating the effects of exercise on physiology will need to establish which parameters they wish to investigate and whether to use voluntary or forced exercise in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…39 In a mouse model of colitis, forced treadmill exercise training aggravated inflammatory indices and outcomes, while voluntary wheel training displayed a protective effect. 40 This suggests a biphasic and dose-response effect of exercise on gut health that has yet to be fully explored in humans.…”
Section: Introductionmentioning
confidence: 99%